ANALISIS MANFAAT EKONOMI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KELANCARAN PENGEMBALIAN KREDIT (STUDI KASUS PADA KOPERASI PERTANIAN SEANDANAN KABUPATEN PESAWARAN) - Roni Mustofa; Dyah Aring Hepiana Lestari; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to analyze the economic benefits, income of rice farming, allocation of credit usage and analyze the factors affecting the chances of the smoothness rate of return at Seandanan Agricultural Cooperatives. The research is conducted at Seandanan Agricultural Cooperative in Pesawaran Regency, Lampung Province, which is determined intentionally.  The research data were taken in July 2019.  This study uses a case study method.  Respondents in this study are 70 rice farmers member of Seandanan Agricultural Cooperative. The data analysis method use descriptive qualitative and quantitative analyses. The results showed that the economic benefits received by members of cooperative in one year is IDR1,711,312.47 and in high category. The average income of rice farming received by members of the Seandanan Agricultural Cooperative in one year has been classified as high, in the amount over cash costs and over total costs, respectively, of IDR17,308,552.78 and IDR16,416,268.56.  Allocation of credit of cooperative membersconsistd of 58.85% for productive activities and the rest, 41.15% for consumptive activities.  Factors that affect the chances of the smoothness rate of credit return by rice farmers members of Seandanan Agricultural Cooperative are the education level of farmers and the allocation of productive credit usage.Key words: agricultural cooperatives, consumptive, credit, and productive